Reactive Palladium-Ligand Complexes for 11C-Carbonylation at Ambient Pressure: A Breakthrough in Carbon-11 Chemistry - Kenneth Dahl; Anton Lindberg; Neil Vasdev; Magnus Schou (MDPI AG, 2023)
The Pd-Xantphos-mediated 11C-carbonylation protocol (also known as the "Xantphos- method"), due to its simplistic and convenient nature, has facilitated researchers in meeting a longstanding need for preparing 11C-carbonyl-labeled radiopharmaceuticals at ambient pressure for positron emission tomography (PET) imaging and drug discovery. This development could be viewed as a breakthrough in carbon-11 chemistry, as evidenced by the rapid global adoption of the method by the pharmaceutical industry and academic laboratories worldwide. The method has been fully automated for the good manufacturing practice (GMP)-compliant production of novel radiopharmaceuticals for human use, and it has been adapted for "in-loop" reactions and microwave technology; an impressive number of 11C-labeled compounds (>100) have been synthesized. Given the simplicity and efficiency of the method, as well as the abundance of carbonyl groups in bioactive drug molecules, we expect that this methodology will be even more widely adopted in future PET radiopharmaceutical research and drug development.